Multiculturalism as a Strategy for National Competitiveness: The Case for Canada and Australia - Ng, Eddy S.; Metz, Isabel (2015)
In this paper, we propose that multiculturalism can serve as an effective public policy tool to enhance a nation’s competitiveness, in an era characterized by financial crises, globalization, immigration, and changing demographics. Specifically, we articulate how multiculturalism and strategic tolerance of differences can promote socioeconomic mobility for individuals, and act as the “glue” that binds immigrants and host country nationals together. We also demonstrate how multiculturalism can attract skilled talents necessary for nation building. Immigrants who retain their ties with their countries of origin (home countries) can serve as natural trade links for their countries of residence (host country) and contribute to a reverse “brain flow” rather than a brain gain/drain for the countries of residence/origin. We conclude by explicating that immigrants can be a source of competitive advantage for countries when a multiculturalism policy is in place.
Keywords: Immigration; National competitiveness; Australia; Canada; Multiculturalism